PENGEMBANGAN SEKTOR PARIWISATA DI KABUPATEN BANYUWANGI TAHUN 2002-2013 - Hisyam Arifal Fahad; Eko Crys Endrayadi (Fakultas Ilmu Budaya Universitas Jember, 2017)
AbstractThis article discusses the development of tourism sector in Banyuwangi regency 2002-2013. The problems in this thesis are (1) the conditions of tourism before the government issues policies; (2) the regional government’s efforts to develop tourism sector; (3) the impact of tourism towards economic, social, and cultural life in Banyuwangi regency. To discuss the problems, this study applies theory of modernization by using the sociology of tourism approach and historical method. Tourism is not merely an activity to find pleasure, but also the source of foreign exchange. One of regencies which can develop tourism industry is Banyuwangi. The development of tourism in this regency, in its early development, experienced fluctuation that was caused by the economic crisis and the tragedy of santet (the killings of many people who were issued having black magic in 1998-1999) that decreased Banyuwangi’s tourism image. Such condition still run until the issue of the 2102 regional government’s regulation as the legal standing of tourism development in Banyuwangi. This regulation has got positive response from the investors that has been showed by the construction of hotel industry, tourism destinations, and transportation which have made Banyuwangi as the centre of emergent economic department in East Java. The growth of tourism has brought new jobs for the society as the managers of tourism services and regrowing local cultures through carnival events conducted by the regional government and society.